Risks factor of Stunting: A Case-Control Study - Sunarto Sunarto; Estuasih Dyah Pertiwi; Dyah Nur Subandriani; Addina Rizky Fitriyanti; Arina Nurul Ihsani; Arwin Muhlishoh; Mohammad Reza Assidhiq (AcTion: Aceh Nutrition Journal, 2025)
Based on the Indonesian Nutritional Status Survey and Indonesian Health Survey data, the prevalence of stunting in Indonesia since 2021 has decreased to 2023 24,4%, 21,6%, and 21,5% by 2023. However, research on the influence of supplementary feeding (SF) on stunting is limited. Thus, this study described the determinants of stunting, including SF consumption in the 6-23 months participant group, as this age group is considered part of The First 1000 days. This case-control study was conducted in the Tlogosari Wetan Community Health Center area, Semarang City, between July and August 2024, with 120 study participants aged 6-23 months (60 stunting cases and 60 controls). The prevalence of stunting at the Tlogosari Wetan Community Health Center was 14,1%. SF had a significant effect on stunting (p<0,023), and early breastfeeding initiation (p=0,053) and breastfeeding (p = 0,073) were weakly associated with stunting. However, per capita income (p=0,116), birth length (0,120), fathers’ education (0,328), and fathers’ body height (p=0,141) had no significant effects on stunting. In conclusion, SF was significantly associated with stunting and accelerated the decline in stunting rate. It is necessary to pay attention to SF consumption to prevent stunting and to increase the knowledge of early initiation breastfeeding (EIB), as it affects the practice of breastfeeding.